Local Identity Intervention in Signage Design: A Case of Sri Baduga Museum - Nur Auliani Puteri Rushar; Wirania Swasty (Humaniora, 2016)
The existence of signage helped visitors to find the desired direction in one area more quickly and easily. With good and systemized signage, visitors could explore the museum even if there was no museum guide. Besides, a less informative, signage of Sri Baduga Museum had not yet had identity which depicted image to the museum. The purpose of this study was to design a signage that was informative and systemized as well as to characterize the local identity. Data were collected through literature study to obtain the theories that support the study. Observations were conducted to some museums to understand the conditions occured more closely. Direct and structured interviews with the museum manager and practitioners were done to reinforce the observations that have been made. Questionnaires were distributed to 100 respondents who had visited and were visiting Sri Baduga Museum to find out their opinions on signage at the museum. Matrix analysis was used to compare four visual objects from four different museums. Kujang (cleaver) as the identity of West Java is used in visual concept. Pictogram shape used came from the stylized shape of Kujang. The form of designed signage and wayfinding derived from stylized ornamentation found on the roof of this museum building. It was expected that the proposed design can produce signage and wayfinding with visual and good continuity to be more informative, interesting, and can give a good impression for visitors.